Hi,
I'm trying to work out how a question was solved from an example in a book.
x(squared)
------------------- = 6.25
6 - 5x + x(squared)
goes to...
5.25x(squared) - 31.25x + 37.5 = 0
I don't understand how this was done.
any ideas?
Hi,
I'm trying to work out how a question was solved from an example in a book.
x(squared)
------------------- = 6.25
6 - 5x + x(squared)
goes to...
5.25x(squared) - 31.25x + 37.5 = 0
I don't understand how this was done.
any ideas?
They have cross multiplied to get the answer.
$\displaystyle \frac{x^2}{6 - 5x + x^2} = 6.25$
$\displaystyle \Rightarrow x^2 = 6.25(6 - 5x + x^2) $ (cross multiply)
$\displaystyle \Rightarrow x^2 = 37.5 - 31.25x + 6.25x^2 $ (expanding)
$\displaystyle \Rightarrow 5.25x^2 - 31.25x + 37.5 = 0 $ (collect terms on one side)